PENGARUH OPINI AUDIT, PROFITABILITAS DAN SOLVABILITAS TERHADAP RETURN SAHAM SEKTOR INFRASTRUKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2018-2020 - Noraida Hafni; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2022)
The study aims to analyze the influence of audit opinion, profitability and solvency through stock returns. The population used in this study are infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. While the sample used in this research is purposive sampling. There are 58 companies included in the infrastructure sector but the sample that can be processed is 39 companies. The results of this study indicate that the audit opinion variable and solvency have an effect on returns , while the profitability variable has no effect on returns stock.Keywords: Opini audit, profitabilitas, solvency, return saham.